Peran Mata Kuliah Modul Nusantara Dalam Peningkatan Sikap Toleransi Mahasiswa Program Pertukaran Mahasiswa Merdeka - Rosyida Nurul Anwar (STKIP PGRI SITUBONDO, 2022)
The Nusantara module is one of the compulsory subjects for students participating in the Independent Student Exchange program. The Nusantara module is a series of activities that focus on creating a comprehensive understanding and introduces the richness of the archipelago's culture from various things. This research aims to find out how the Nusantara Module Course plays a role in increasing students' cultural tolerance. This study uses a qualitative approach. The subjects of this study were inbound students at the Independent Student Exchange Program at the University of PGRI Madiun in 2021. Data collection used observation, interviews, and documentation. The results showed that the Nusantara Module course had a role in increasing the cultural tolerance attitude of inbound students through; first, the philosophy of respecting and respecting the culture of others; second, do not belittle or elevate one tribe over another; third, assuming all tribes are brothers and sisters; fourth, not to discriminate, and to treat everyone equally and equally.